Effectiveness of using the dose of mycorrhiza bio-fertilizers to increase growth and production of red paprika (Capsicum annum L.) in Ultisol Aceh. Issue 1 (November 2021) - Syafruddin, S; Syakur, S; Jumini; Sulaiman, I
Abstract: Using dose mycorrhizal bio-fertilizers can spur the growth and production of red paprika ( Capsicum annum L.) on Ultisol Aceh. Besides that, it can also increase root colonization by mycorrhizal and P2O5 uptake, which red paprika plants need to produce high growth and yield. The purpose of this research was to study the effect of dose bio-fertilizer mycorrhizal on the growth and production of red paprika in Ultisols Aceh. The research was arranged by a non-factorial randomized block design with three replications. The investigated factor was the dose of bio-fertilizer mycorrhizal from local specific strain mixing between Glomus mosseae and Gigaspora sp . The dose of the mycorrhizal bio-fertilizer used was control (without mycorrhizal) of each plant, 5, 10, and 15 gram. The observed parameters were plant height and stem diameter of red paprika at 15, 30, and 45 days after transplanting; additionally, the parameter of red paprika production was observed at 125 days after transplanting and P2 O5 uptake and root colonization by mycorrhizae at 60 days after transplanting. The results showed that the best dose of mycorrhizal bio-fertilizers on growth and production, root colonization, P2 O5 uptake was found in the treatment of doses of 10-gram mycorrhizal bio-fertilizer for each plant.